Gender, International Relations, and the Development of Feminist Security Theory. - Blanchard, Eric M. (Signs: Journal of Women in Culture & Society)
Surveys the feminist literature on international relations on international security highlighting the functions of feminist scholarship in any disciplinary intervention. Reconceptualization of core concepts; Explanation of the exclusion of women from foreign policy decision; Strategies for getting more access to power.